2018
DOI: 10.4049/jimmunol.1601808
|View full text |Cite
|
Sign up to set email alerts
|

mPGES1-Dependent Prostaglandin E2 (PGE2) Controls Antigen-Specific Th17 and Th1 Responses by Regulating T Autocrine and Paracrine PGE2 Production

Abstract: The integration of inflammatory signals is paramount in controlling the intensity and duration of immune responses. Eicosanoids, particularly PGE, are critical molecules in the initiation and resolution of inflammation and in the transition from innate to acquired immune responses. Microsomal PGE synthase 1 (mPGES1) is an integral membrane enzyme whose regulated expression controls PGE levels and is highly expressed at sites of inflammation. PGE is also associated with modulation of autoimmunity through alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“… 67 Quite recently, it was also reported that mPGES1 is involved in generation of antigen-specific T H 17 cells by regulating PGE 2 production in a T-cell autocrine and paracrine manner. 68 Our present findings combined with these findings suggest that PGE 2 plays an important role in psoriasis through regulation of antigen-specific pathogenic T H 17 cells.…”
Section: Discussionsupporting
confidence: 79%
“… 67 Quite recently, it was also reported that mPGES1 is involved in generation of antigen-specific T H 17 cells by regulating PGE 2 production in a T-cell autocrine and paracrine manner. 68 Our present findings combined with these findings suggest that PGE 2 plays an important role in psoriasis through regulation of antigen-specific pathogenic T H 17 cells.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies suggest that inhibition of mPGES1 activity resulted in reduced PD-L1 expression in myeloid cells infiltrating bladder tumor tissue [33]. Furthermore, expression of mPGES1 is necessary for induction of T regs and IL-17-producing T cells during primary immune response [103]. Altogether, these data indicate that targeting mPGES1 in bladder cancer could reduce the tumor-associated immunosuppression and improve the efficacy of cancer immunotherapy.…”
Section: Mpges1mentioning
confidence: 89%
“…It remains unknown which mechanisms trigger Th17 cell accumulation in AS. PGE 2 can induce Th17 cells through EP2 and EP4 receptor signaling [21][22][23][24][25][26]. It has been recently shown that EP2 and EP4 signaling is critical in Th17mediated autoimmune inflammation of the skin [25].…”
Section: Introductionmentioning
confidence: 99%